Cigarette Smokers as Job Risk Takers - Viscusi, W. Kip; Hersch, Joni (The Review of Economics and Statistics, 2001)
Using a large data set, the authors find that smokers select riskier jobs, but receive lower total wage compensation for risk than do nonsmokers. This finding is inconsistent with conventional models of compensating differentials. The authors develop a model in which worker risk preferences and job safety performance lead to smokers facing a flatter market offer curve than nonsmokers. The empirical results support the theoretical model. Smokers are injured more often controlling for their job's objective risk and are paid less for these risks of injury. Smokers and nonsmokers, in effect, are segmented labor market groups with different preferences and different market offer curves. © 2001 by the President and Fellows of Harvard College and the Massachusetts Institute of Technology